Methodology to analyse national food system based on secondary reports and data used by organizations in developing future strategies. - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Methodology to analyse national food system based on secondary reports and data used by several organizations in developing future strategies, characterizing sub-national food systems, and analyzing the national consumer and food environment